Sen and the art of quality of life maintenance: towards a working definition of quality of life - Ruta, D; Camfield, L; Donaldson, C (Wellbeing in Developing Countries Research Group, 2006)
The capability approach advocated by Amartya Sen provides a new philosophical framework for social policy. It also permits re-appraisal of a central concept in health and social care, and more recently international development - 'quality of life'. This paper begins by comparing Sen's capability view of quality of life with current views predominant in health care, and re-defines quality of life as 'the gap between desired and actual capabilities'. A causal pathway linking resources such as income, to capabilities (including health), and finally to quality of life, is postulated. The notion of 'cognitive homeostasis' is introduced to explain how a curvilinear relationship is observed between resources, capabilities, and quality of life. A separate set of factors (eg: spirituality, loss of a partner, chronic pain) is identified that act to sustain or destabilise the cognitive homeostatic mechanism. The paper concludes by examining some of the implications of this final causal model for social justice and policy evaluation.